Association of intraoperative hyperglycemia with postoperative composite infection after cardiac surgery with cardiopulmonary bypass: A retrospective cohort study - Xiong, Xinglong; Chen, Dongxu; Cai, Shuang; Qiu, Li; Shi, Jing (Frontiers in Cardiovascular Medicine, 2023)
Background: Cardiac surgery with cardiopulmonary bypass (CPB) carries an increased risk of morbidity and mortality due to postoperative infections. Therefore, identification of the modiﬁable factors remains a priority. Moreover, the association between intraoperative hyperglycemia (IH) and postoperative infections in patients undergoing cardiac surgery with CPB is inadequately studied. Methods: Adult patients were retrospectively enrolled who underwent cardiac surgery with CPB at our institution between June 1, 2019 and July 30, 2021. A total of 3428 patients were enrolled to evaluate the association of IH (blood glucose ≥ 180 mg/dL) with postoperative infection in patients. Moreover, the new onset of any type of infection during the hospital stay was determined. Further, the optimal cutoff values of intraoperative glucose to predict in-hospital infection were determined. Results: The composite outcome occurred in 497 of 3428 (14.50%) patients. It was observed that IH was associated with an increased risk of postoperative composite infection [adjusted odds ratio: 1.39, (95% confidence interval), 1.06-1.82, P = 0.016]. Restricted cubic splines were applied to flexibly model and visualize the association of intraoperative peak glucose with infection, and a J-shaped association was revealed. Besides, it was demonstrated that the possibility of infection was relatively flat till 150 mg/dL glucose levels which started to rapidly increase afterwards. Conclusions: We summarize that IH is associated with an elevated risk of postoperative new-onset composite infections in patients undergoing cardiac surgery with CPB. Further, our findings suggested that perioperative blood glucose management should be more stringent, i.e., lesser than 150 mg/dL.